Metaverse Architectures: A Comprehensive Systematic Review of Definitions and Frameworks - Cemile Boztas; Essam Ghadafi; Rasha Ibrahim (Future Internet, 2025)
The metaverse is a multidimensional reality space that represents the evolving interface between humans, digital systems, and spatial computing. This research aims to provide a comprehensive synthesis of metaverse definitions and architectural frameworks through the analysis of academic literature. A systematic literature review of 103 peer-reviewed studies was conducted, from which 33 explicit definitions and 25 architectural models were selected for detailed analysis. A mixed-methods qualitative approach was employed, combining a systematic literature analysis, word frequency analysis, and a thematic analysis to develop an expanded conceptual and architectural understanding. The analysis of 33 definitions revealed eight recurring conceptual themes, which were synthesised into five overarching categories: conceptual and linguistic constructs, spatial-environmental design, technological orientation, economic and governance systems, and social and human interaction. A total of 25 studies proposing architectural models are categorised into three thematic groups: technology-based, domain-based and layered architectures. A significant contribution of this study is the categorisation and comparative evaluation of foundational architectural models, specifically the extensively referenced three-, four-, and five-layer frameworks. The findings are structured around two primary areas of focus: the conceptual definition and the comparative analysis of established metaverse architecture models, focusing on a set of well-established models that exhibit conceptual clarity, structural coherence, and widespread acceptance in the literature. This integrated methodological approach not only offers a dual-perspective analysis that bridges conceptualisation and system design but also introduces an analytical framework that supports future standardisation and governance discussions.